Comparison of Soot Particle Movement based on Crank Angle - Hanafi, M.H.M; Wan Mahmood, W.M.F; Abdollah, Mohd Fadzli bin; Saleman, Abdul Rafeq; Nor, N.F.M; Zulfattah, Z. M.; Shamsudin, S.A; Ibrahim, A. (Elsevier, 2013)
In a diesel engine, soot was produced due to incomplete fuel combustion in a combustion chamber. Some of this soot sticks to the cylinder wall and interferes with lubricant oil. This soot causes the lubricant oil to contaminate and this increases its viscosity. Contamination of lubricant oil is one of the major causes of engine wear. Therefore, the focus of this study is on soot movement in diesel engine that is the initial step to avoid contamination of lubricant oil. This work uses the data of the formation of soot particles from Kiva-3 v obtained from previous investigation and then simulated it by a Matlab routine. Kiva-3 v produced velocity vectors of the soot, fuel, temperature, pressure and others. Matlab routine uses trilinear interpolation and fourth order Runge Kutta method in order to calculate soot movement in a combustion chamber. In addition, the influence of drag force is considered in the calculation to achieve a higher accuracy. The objective of this study is to compare soot particle movement between 8° ATDC and 18° ATDC. Results show that 8° ATDC has a high risk to contaminate lubrication oil in certain location compare to 18° ATDC.